1998
DOI: 10.1121/1.421212
|View full text |Cite
|
Sign up to set email alerts
|

A numerical and experimental investigation of the performance of sound intensity probes at high frequencies

Abstract: The influence of scattering and diffraction on the performance of sound intensity probes has been examined using a boundary element model of an axisymmetric two-microphone probe with the microphones in the usual face-to-face arrangement. On the basis of calculations for a variety of sound field conditions and probe geometries it is concluded that the optimum length of the spacer between the microphones is about one microphone diameter; with this geometry the effect of diffraction and the finite difference erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 13 publications
0
31
0
8
Order By: Relevance
“…10 Much later it was discovered that the effect of scattering and diffraction not only tends to counterbalance the finite-difference error but in fact for a certain length of the spacer almost perfectly cancels it under virtually any sound field condition encountered in practice. 11 A practical consequence is that the upper frequency limit of a sound intensity probe based on two 1 / 2 in. microphones separated by a 12 mm spacer in the face-to-face arrangement is about 10 kHz, which is about an octave higher than the frequency limit determined by the finite-difference approximation.…”
Section: The P-p Measurement Principlementioning
confidence: 99%
See 1 more Smart Citation
“…10 Much later it was discovered that the effect of scattering and diffraction not only tends to counterbalance the finite-difference error but in fact for a certain length of the spacer almost perfectly cancels it under virtually any sound field condition encountered in practice. 11 A practical consequence is that the upper frequency limit of a sound intensity probe based on two 1 / 2 in. microphones separated by a 12 mm spacer in the face-to-face arrangement is about 10 kHz, which is about an octave higher than the frequency limit determined by the finite-difference approximation.…”
Section: The P-p Measurement Principlementioning
confidence: 99%
“…microphones separated by a 12 mm spacer in the face-to-face arrangement is about 10 kHz, which is about an octave higher than the frequency limit determined by the finite-difference approximation. 11 The combination of 1 / 2 in. microphones and a 12 mm spacer is now regarded as optimal, and longer spacers are only used when the focus is exclusively on low frequencies.…”
Section: The P-p Measurement Principlementioning
confidence: 99%
“…11. However, since windscreens have no influence on sound intensity measurements except at fairly low frequencies 4 where the probe does not change the sound field at all, 11 the intensity is simply calculated from the pressure at two points that represent the two microphones, that is, from the expression…”
Section: B Coupled Boundary Element Modelmentioning
confidence: 99%
“…2 In 1998 it was found that the effect of scattering and diffraction tends to counterbalance the finitedifference error under virtually any sound field condition that can be encountered in practice. 3 It was shown that the practical upper frequency limit of a sound intensity probe based on two 0.5 in. microphones separated by a 12 mm spacer in the face-to-face arrangement is about 10 kHz, 3 which is about an octave higher than the frequency limit determined by the finite-difference approximation.…”
Section: Introductionmentioning
confidence: 99%
“…3 It was shown that the practical upper frequency limit of a sound intensity probe based on two 0.5 in. microphones separated by a 12 mm spacer in the face-to-face arrangement is about 10 kHz, 3 which is about an octave higher than the frequency limit determined by the finite-difference approximation.…”
Section: Introductionmentioning
confidence: 99%